MODEL OF ISLAMIC SOCIAL ENTREPRENEURSHIP IN FAMILY BUSINESS - Muhammad Agus Setiawan; Sheema Haseena Armina; Mufti Afif (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The purpose of this research in to outline an Islamic Social Entrepreneurship (ISE) development model in a family business in Ponorogo’s Setono Chicken Satay Village as a study case. This study employs a descriptive qualitative methodology with a case study approach. The ISE development model means that this family business in the Setono Ponorogo chicken satay village has implemented crucial elements in the ISE that are related to four dimensions, including economic, religious, social, and cultural dimensions. These four dimensions are integrated in terms of meeting material needs for daily life, non-material needs, such as worship and personal social responsibility (PSR), communication and community among neighbours and businessmen and then maintaining ancestral cultural values that have been passed down to them. The originality of this study that the concern on filling the answer about business and Islamic teachings itself. Hence, every business has its own potential and originality, it will build a model of the business